School Management – a Case Study of Municipal Corporation of Delhi (MCD) School - SUBHASH, P.D.; ANWAR, M. SIRAJ (THE PRIMARY TEACHER, 2015)
Effective management of a school plays pivotal role in bringing desirable changes in the overall functioning of the school and in achieving the aims and objectives set by the curriculum planners and administrators. This study critically analyses the functioning of the school management system in a Municipal Corporation of Delhi (M.C.D.) School. The study reveals that Municipal Corporation of Delhi (M.C.D.) makes serious efforts to provide proper directions to head teachers and teachers in managing the school activities in a better way. However, it also points out the lacunae existing and the need for the improvement of the management of curriculum. The study also recommends the necessity of combined efforts of teachers, parents, members of Vidyalaya Kalyan Samiti, local community members and M.C.D. officials for attaining the educational objectives